(untitled) (Journal of the College of Basic Education, 2023)
When God Almighty created the creation, He did not leave them floundering in the darkness of ignorance and the labyrinths of misguidance; Rather sendTo them are Messengers who guide them to the truth and warn of the abyss of evil.Others, including Khalil al-Rahman, the father of the prophets, Ibrahim (may God have mercy on him), whom his Lord praised and commanded our Prophet to follow.He said: ((Indeed, Abraham was a nation obedient to God, upright, and he was not of the polytheists; thankful for his grace, choosing him and guiding him tostraight path; And We gave him good in this world, and in the Hereafter he will be among the righteous. Then We inspired you to follow a religionIbrahim Hanifa, and he was not of the polytheists)”); Ibrahim (Ayah Sadam) was mentioned ninety-nine times in the Qur’an.Al-Karim distributed over twenty-five surahs ©. Here I will present the aesthetics of the story of our master Irahim Mar’i’i dam,(which appears in his biography according to what was stated in the Holy Qur’an. The Qur’an is the main source of legislation. He came up with the story and the scenes of this world and the Hereafter in a miraculous manner and imagesan aesthetic with an accurate literary portrayal; Perhaps Al-Jahiz (d. 255 AH) was the first to explain the Qur’anic aesthetics in his formatfar away and its beautiful arrangement!; And he followed him in that rhetoric (d. 388 AH), but through the beauty of the words, even if he was not neglectedThe role of meanings in their impact on the recipient’). As for Al-Baqalani (403 AH), he notes the aesthetic characteristic of patternsAll of the Qur’an is without discrepancy or discrepancy, and it is the beauty of the wondrous systems that masters are unable to matchClip and literature! . Al-Jurjani (d. 482 AH) later warned of the Arabs’ fascination with a single beautyFor the Qur’an, which applies to its words, verses, surahs, and their syllables. Accordingly, the Qur’anic aesthetic is the science of Qur’anic aesthetics